A Comprehensive Review on Homoeopathic Miasmatic Interpretation of Autoimmune Disorders - Parmar, Divya (Achievements and Challenges of Medicine and Medical Science Vol. 7, 2024)
A condition known as an autoimmune disorder is one in which the immune system reacts abnormally and incorrectly targets and attacks healthy, functional elements of the body as though they were foreign organisms. There are almost 100 different types of autoimmune illnesses, some of which are organ-specific (like primary biliary cirrhosis, or PBC) and others of which are multi-organ immunological diseases, like systemic lupus erythematosus, or SLE. It is also shown that the majority of patients with autoimmune diseases experienced severe stress as children and, more crucially, a lack of ability to act out, express, and externalize the stress, or an insufficient catharsis of the feeling. The greatest treatment for autoimmune illnesses is reportedly homoeopathy. In homoeopathy, every illness is intrinsic and general, affects the patient as a whole, and requires internal treatment. It effectively treats and prevents the needless amputation of good tissues. Homoeopathy is a completely natural procedure that has been doing marvels for centuries.